2022
DOI: 10.2188/jea.je20200260
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Long-term Weight Change Since Midlife and Risk of Incident Disabling Dementia Among Elderly Japanese: The Ohsaki Cohort 2006 Study

Abstract: Background Both weight loss and cognitive impairment are common in late-life, but it remains unknown whether weight change is associated with risk of incident dementia among elderly Japanese. Our study aimed to investigate the association between long-term weight change since midlife and risk of incident disabling dementia using a community-based cohort study of elderly Japanese. Methods In 2006, we conducted a cohort study of 6,672 disability-free Japanese adults aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Therefore, it is unlikely that the observation of pre-dementia weight loss is an artifact of one-year accelerated weight loss due to preclinical cognitive decline [ 30 ]. This also suggests that our finding aligns with previously conducted research that suggests that a higher degree of weight loss can be observed in patients several years before a diagnosis of dementia [ 7 , 8 , 9 , 11 , 30 ]. Our results are also in agreement with two recent publications using different analytical approaches that identified pre-diagnosis weight changes as a predictor of dementia [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it is unlikely that the observation of pre-dementia weight loss is an artifact of one-year accelerated weight loss due to preclinical cognitive decline [ 30 ]. This also suggests that our finding aligns with previously conducted research that suggests that a higher degree of weight loss can be observed in patients several years before a diagnosis of dementia [ 7 , 8 , 9 , 11 , 30 ]. Our results are also in agreement with two recent publications using different analytical approaches that identified pre-diagnosis weight changes as a predictor of dementia [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study conducted by LeBlanc et al (2017) observed a greater rate of weight loss (on average additional −0.11 kg/year) over 20 years in women before a diagnosis of mild cognitive impairment (MCI) and dementia [ 8 ]. A recent study conducted in 2020 by Lu et al also suggested that long-term weight loss (≥1.5 kg) can be detected 12 years prior to a diagnosis of disabling dementia in a Japanese population [ 9 ]. These studies suggest that weight loss during middle adulthood may serve as a prognostic factor of future cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that have explored the association between weight change in late life and dementia mostly observed an increased dementia risk linked to weight loss ( 14–16 , 19 , 27 , 33 , 34 ). Conversely, in some studies, weight gain has been either not significantly related to dementia or seemed to be with reduced dementia risk ( 15 , 19 , 35 ). A recent meta-analysis pooling data from 19 prospective cohorts and 4 clinical trials showed that older adults (aged ≥60 and older) with ≥0.5% annual weight loss had approximately one-third greater risk of all-cause dementia than those with a relatively stable weight.…”
Section: Discussionmentioning
confidence: 96%
“…The typical study was a cohort of healthy older adults, with information from unique questionnaires, interviews, health check-up data, other measurement data measurements and medical claims as the exposure and LTC certification or care needs level data as the outcome . Additionally, several similar studies with the independent degree of daily living for older adults with dementia as an outcome were conducted (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Easily applicable research like this is expected to continue to be widely conducted.…”
Section: Discussion Of Current Status and Perspectives Of Studies Usi...mentioning
confidence: 99%